An Analysis of Idiomatic Expressions found in The Lightning Thief Song Lyrics - Radesman Lingga, Thomson; Riana Savitri, Ferra (Universitas Pasundan, 2024)
The title of this study is An Analysis of Idiomatic Expressions Found In “The Lightning Thief (Original Cast Recording)” Song Lyrics. The objective of this study is to analyze the existence of idioms inside of an existing work of literature in the form of songs as part of a musical play and what the idiom classified as, specifically what set them apart from each other and what pattern made them classified as one type through their semantic side. This study also includes an analysis of idiomatic expressions in the form of idiom references as it is considered part of the character’s personal touch as part of a story. Through a qualitative research method, the writer gathers and analyzes each idiom that exists based on listed idioms of the fourth edition of the Oxford Dictionary of Idioms by John Ayto to separate them into 3 idiom classifications made by Cacciari & Glucksberg in 1991 to those Compositional Opaque, Compositional Transparent, and Quasi Metaphorical. Each type is sometimes difficult to classify, possibly due to the existence of either phrasal verbs or individual words that have multiple meanings.